Prepartum Eclampsia in a Tibetan Crossbred Bitch - A case Report - JANA, D; JANA, M; CHAKRABORTY, D (The Indian Journal of Animal Reproduction, 2023)
A primiparous Tibetan crossbred bitch (Tibetan spaniel X Lhasa - Apso) named Julli aged about four years was brought to the Block Veterinary Dispensary with ahistory of 6 5 days pregnancy andassociated complaints of fever, anorexia, restlessness and convulsions. The owneralso reported that there were intermittent discharge of clearfluid per-vagina four· daysear lier. The bitch was in eclamptic convulsion and in recumbant state. Twitching of muscles of face, tongue andlimbs and stertorous breathing with frothy secretions filling the mouth were noticed. This followed muscular rigidity andoccasional tremors. Pupils were dilated. Typical panting with exagerated respirationwas predominant. Face seemed to be distorted after few seconds of convulsions. Legs were inverted. Hyperthermia with rectal temperature 104.5°F was recorded. The tongue held protruded on one side and licking movement was absent. Clinical examination r.evealed the enlarged abdomenand engorged mammary gland. Milkappeared in all the teats. Foetal heart sound was not audible. Per abdominal examination revealed no foetal movement. Per vaginal examination revealed closed cervix with soft texture without any straining.
Keywords: Prepartum Eclampsia; Tibetan Crossbred Bitch